Achieve clean and efficient biomethane production by matching between digestate recirculation and straw-to-manure feeding ratios. (1st August 2020) - Zheng, Zehui; Cai, Yafan; Zhao, Yubin; Meng, Xingyao; Zhang, Yue; Lu, Chungui; Hu, Yuegao; Cui, Zongjun; Wang, Xiaofen
Abstract: Liquid digestate recirculation can fundamentally solve the problem of voluminous liquid digestate discharge for biogas projects. However, the uncertainty of the effect of recirculation under different feedstock restricts the application of recirculation technology. In this study, the comprehensive effects of straw to manure feeding ratios and liquid digestate recirculation on anaerobic digestion performance and microbial community structure were investigated. Recirculation was beneficial for biomethane production and digestion stability in digesters of corn stalk and straw/manure 3:1 by alleviating the loss of ammonia and alkalinity, while it aggravated the accumulation of ammonia and organic acids and reduced methane yield under 1:1, 1:3 and pig manure. The feeding ratios and recirculation formed a combined effect on ammonia concentration in the fermentation system, and when the total ammonia concentration was above 1500 mg/L, acids accumulation and decline in methane production would occur whether with recirculation or not. The microbial community structure varied corresponding to the fermentation state. In the well-run digesters, which were 3:1 with recirculation and 1:1 without recirculation, the dominant methanogens were Methanosaeta, while in the inhibited digesters, Methanosarcina and Methanosphaera dominated the methanogen community. Based on producing 1 GJ energy, the strategy of 3:1 with recirculation reduced the discharge of liquid digestate by 81.9% and the use of clean water by 65.4% compared to that of 1:1 without recirculation. An integrated approach of adjusting feedstock formula and selectively employing liquid digestate recirculation was proposed to produce liquid digestate on-demand with downstream application requirement, which will make biogas industry eco-friendly and cost-effective. Graphical abstract: Image 1 Highlights: Cross effects of liquid digestate reuse and feed-formula on performance and microbes. Recirculation is beneficial when straw to manure ratio is 3:1 or higher in feedstock. Recirculation mode ran well and reduced 81.9% liquid discharge and 65.4% water usage. Cooperation of feedstock and recirculation may achieve controllably liquid discharge.